Total and Partial Factor Productivity of Forest Enterprises and Nurseries with the Ramsay Model: Example of Istanbul Regional Directorate of Forestry - Kaya, Güven; Ok, Kenan; Porsuk, Tuncay (Bartın Üniversitesi, 2024)
Although there have been many studies on measuring the productivity of state forest enterprises in Turkey, it has not been reflected in practice. Productivity calculation methods that are applicable and based on accounting data need to be developed. In this article, it was aimed to calculate the partial productivity, multifactor productivity and total factor productivity measures of 10 forest management directorates and 2 nursery directorates affiliated to Istanbul Regional Directorate of Forestry using the Ramsay model, to compare the findings and to discuss the ways of improvement for better management practices. The analysis was based on the revolving fund accounts of the enterprises and nurseries between 2018 and 2022. In each partial productivity measure, a different management unit outperformed the others, while Demirköy enterprise stood out in total and detailed productivity measures. It was also observed that the findings of the Ramsay model could not be evaluated independently of the levels of normal and total forest area or forest volume owned by the enterprises. Compared to the physical and monetary productivity measures in the literature that have been previously used for forest enterprises, the Ramsay model is based on accounting data and is easy to calculate, making it a viable and practical opportunity for productivity measurements required for forest enterprises and nurseries. However, the difference tests revealed that the values calculated for the enterprise and nurseries were statistically different. As a result, it was seen that the Ramsay model is suitable for productivity measurements in all forest enterprises and nurseries, but structural differences should be taken into account when ranking corporate governance effectiveness and success among institutions.

Türkiye'de devlet orman işletmelerinin verimliliklerinin ölçümüne yönelik birçok araştırma olmasına rağmen, uygulamaya yansımamıştır. Uygulanabilir ve muhasebe verilerine dayanan verimlilik hesaplama yöntemlerinin geliştirilmesi gerekmektedir. Bu makalede İstanbul Orman Bölge Müdürlüğüne bağlı 10 orman işletme müdürlüğü ve 2 fidanlık müdürlüğünün kısmi verimlilik, çok faktörlü verimlilik ve toplam faktör verimliliği ölçütlerinin Ramsay modeli kullanılarak hesaplanması, bulguların karşılaştırılması ve daha iyi yönetim uygulamalarına yönelik iyileştirme yollarının tartışılması amaçlanmıştır. Analizler işletmelerin ve fidanlıkların 2018-2022 yılları arasındaki döner sermaye hesaplarına dayanmıştır. Her bir kısmi verimlilik ölçüsünde farklı bir yönetim birimi diğerlerinden iyi durumdayken, toplam ve ayrıntılı verimlilik ölçülerinde Demirköy işletmesi öne çıkmıştır. Ayrıca Ramsay modeli bulgularının; işletmelerin sahip olduğu normal, toplam orman alanı veya ağaç serveti düzeylerinden bağımsız değerlendirilemeyeceği görülmüştür. Literatürde yer alan ve orman işletmeleri için daha önce kullanılmış fiziki ve parasal verimlilik ölçütlerine kıyasla Ramsay modelinin; muhasebe verilerine dayanması ve hesaplama kolaylığı açılarından orman işletmeleri ve fidanlıklar için gerekli verimlilik ölçümleri için uygulanabilir ve pratik bir fırsat sunduğu görülmüştür. Bununla birlikte, yapılan fark analizleri, işletme ve fidanlıklar için hesaplanan değerlerin farklı olduğunu ortaya koymuştur. Sonuç olarak Ramsay modelinin, tüm orman işletmeleri ve fidanlıklarda verimlilik ölçümleri yapmaya uygun olduğu ancak kurumsal yönetim etkinliği ve kurumlar arası başarı sıralaması yaparken, yapısal farklılıkların dikkate alınması gerektiği görülmektedir.
Ramsay Modeli ile Orman İşletme ve Fidanlıklarının Toplam ve Kısmi Faktör Verimlilikleri: İstanbul Orman Bölge Müdürlüğü Örneği
10.5307/2021-2022-2023
Keywords: Forestry Politics; Economics and Law; Ormancılık Politikası; Ekonomisi ve Hukuku